Spatial analysis on the occurrence of inshore and offshore bottlenose dolphins (Tursiops truncatus) in Osa Peninsula waters and Golfo Dulce, Costa Rica - Pacheco-Polanco, Juan Diego; Oviedo Correa, Lenin; Fernandez, Marc; Herra-Miranda, David (The journal of cetacean research and management, 2020)
The aim of this assessment is to advance our understanding in the spatial ecology of the resident inshore and offshore population of bottlenosedolphins in Golfo Dulce (GD) and Osa Peninsula Waters (OPW). Our approach used niche-based models (Phillips et al., 2006, Thorne et al., 2012,Friedlaender et al., 2011), which provided details of how dolphins use coastal and oceanic habitats, describing the factors that influence theirdistribution in the study area and identifying the critical habitats to be considered for management and conservation. Our analyses indicate severalimportant aspects of the distribution of these two ecotypes of bottlenose dolphins. As expected in the study area, these two ecological races occurin close proximity, but differ in the structural factors of the habitat they occupy. The inshore population uses areas close to the mouths of the riversas critical foraging habitats, being influenced by tidal cycles and seasonal changes in water temperature and salinity. The offshore population inoceanic habitats must rely on prey species found in rare but profitable patches, therefore pelagic dolphins in the open ocean would often need totravel long distances searching for these patches. Distribution models illustrating the difference in habitat use presented in this assessment are keyto effective management of the marine mammals’ diversity in Costa Rica.